Preparation method and application of natural polysaccharide-based micro-nano motor

By using natural polysaccharide-based micro-nanomotors as carriers, the problem of limited application of curcumin in food is solved, and the stable embedding and slow release of curcumin is achieved, which improves its bioaccessibility and anti-inflammatory activity.

CN119732496APending Publication Date: 2025-04-01DALIAN POLYTECHNIC UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411875697.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing food active ingredients such as curcumin are limited in food applications. Due to its low water solubility, insufficient dispersion and easy to decompose under adverse environments, and traditional delivery systems such as microemulsions have poor stability during storage, it is impossible to achieve slow release of specific parts.

Method used

Natural polysaccharide-based micro-nanomotors are used as the carrier of curcumin to prepare polysaccharide microtubules by template method, and enzyme-driven, magnetic-driven and platinum-driven micro-nanomotors are prepared by glutaraldehyde cross-linking method, magnetic nanoparticle modification and other methods to achieve stable embedding and slow release of curcumin.

Benefits of technology

It improves the thermal stability and photostability of curcumin, achieves slow release in specific parts of the body, enhances biological accessibility, and significantly inhibits the inflammatory response, demonstrating good anti-inflammatory activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119732496A_ABST
    Figure CN119732496A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a natural polysaccharide-based micro-nano motor, and the method comprises the following steps: (1) preparing a polysaccharide-based microtube: taking a polycarbonate film as a template, and forming an alternately assembled film layer of chitosan and kappa-carrageenan on the template through a soaking assembly method or a pressure assembly method; (2) preparation of a nano-motor: cross-linking glucose oxidase on the polysaccharide-based microtube through a glutaraldehyde cross-linking method to form an enzyme-driven micro-nano-motor; or the ferroferric oxide and the polysaccharide-based microtube are crosslinked to form a magnetic drive micro-nano motor; or the nano platinum and the polysaccharide-based microtube are crosslinked to form the platinum-driven micro-nano motor. The preparation method disclosed by the invention is simple and safe, the prepared micro-nano motor has good autonomous motion performance and also has load performance so as to avoid degradation of effective active components, and the magnetically-driven and platinum-driven micro-nano motor has excellent photothermal conversion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of food science and technology, and in particular relates to a preparation method of a natural polysaccharide-based micro-nano motor and application thereof. Background Art

[0002] Food active ingredients refer to bioactive compounds that exist in food and have health-promoting effects, including essential nutrients such as vitamins, fatty acids and amino acids; chemicals in plants such as terpenes, polyphenols, phytosterols and alkaloids; and active compounds produced by food processing such as biological peptides. Curcumin is a polyphenol compound extracted from the natural product turmeric. It has low water solubility and insufficient dispersibility in food systems. During food processing and storage, it will quickly decompose when exposed to adverse environments, resulting in its application in food being restricted. This is also the limitation of most food active ingredients. The solution is usually to use traditional delivery systems, mainly including microemulsions, liposomes, micelles, hydrogels, etc. to encapsulate them. For example, microemulsions can be used to encapsulate food active ingredients by relying on passive diffusion transport of carriers and active ingredients, preventing them from being degraded in the gastrointestinal environment and improving tolerance. However, microemulsions are prone to Ostwald ripening and flocculation during storage, resulting in poor stability, incomplete encapsulation, and the inability to achieve slow release of food active ingredients in specific parts of the body.

[0003] At present, nanoemulsions with small and uniform particle sizes have been developed using equipment such as high-pressure microfluidization and high-pressure homogenization, which significantly improves the embedding rate of food active ingredients. Researchers used sodium caseinate and modified lecithin to homogenize under high pressure to manufacture water-in-oil nanoemulsions loaded with astaxanthin, which showed good chemical and physical stability in a wide range of temperature and pH concentrations and during storage. However, due to the small contact area between the aqueous phase and the oil phase, the structure of sensitive food active ingredients changes and reduces chemical stability. At the same time, excessive loading of fat-soluble active ingredients will also produce toxicity. In addition, delivery systems developed in recent years, such as metal-organic frameworks (MOFs) and hydrogels, have provided new methods for achieving precise delivery. For example, MOF encapsulates curcumin, achieves a high loading effect and stable release in the gastrointestinal tract, but the preparation of MOF raw materials and chemical cross-linking are limited in food due to the presence of reagents that are harmful to biological activity.

[0004] Micro-nano motors are powered machines that use different energy sources such as chemical energy, light energy, and thermal energy to convert into mechanical kinetic energy to achieve autonomous movement. It is reported that micro-nano motors have broad application potential in many fields, including drug delivery, environmental monitoring, biomedical imaging, etc., but their application in the food field needs further supplementation and expansion. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a method for preparing a natural polysaccharide-based micro-nano motor and its application. The micro-nano motor of the present invention, as a carrier of curcumin, has a certain anti-degradation effect on it. Compared with free curcumin, the micro-nano motor-curcumin loading system has stronger thermal stability and light stability.

[0006] The technical solution of the present invention is as follows:

[0007] The first object of the present invention is to provide a method for preparing a natural polysaccharide-based micro-nanomotor, comprising the following steps:

[0008] (1) Preparation of polysaccharide-based microtubules: Using a polycarbonate membrane as a template, an alternating assembly layer of chitosan and κ-carrageenan is formed on the template by an immersion assembly method or a pressure assembly method, and then the template is washed away to obtain polysaccharide-based microtubules;

[0009] (2) Preparation of micro-nanomotors: Glucose oxidase is cross-linked to polysaccharide microtubules by glutaraldehyde cross-linking method to form enzyme-driven micro-nanomotors; alternatively, ferroferric oxide is cross-linked to polysaccharide microtubules to form magnetically driven micro-nanomotors; alternatively, nanoplatinum is cross-linked to polysaccharide microtubules to form platinum-driven micro-nanomotors.

[0010] In one embodiment of the present invention, in step (1), the pore size of the polycarbonate membrane is 600 nm and the thickness is 9 μm.

[0011] In one embodiment of the present invention, in step (1), the immersion assembly method is: the template is repeatedly and alternately immersed in a chitosan solution and a κ-carrageenan solution to perform self-assembly; then the template is washed away to obtain polysaccharide-based microtubules.

[0012] In one embodiment of the present invention, in step (1), the pressure assembly method is: chitosan solution and κ-carrageenan solution are repeatedly and alternately added to the template, and then filtered and assembled; and then the template is washed away to obtain polysaccharide-based microtubules.

[0013] In one embodiment of the present invention, the concentration of the chitosan solution is 1 mg / mL; the concentration of the κ-carrageenan solution is 1 mg / mL; and N,N-dimethylformyl is used to dissolve the template.

[0014] In one embodiment of the present invention, in step (1), the method for preparing polysaccharide-based microtubules by immersion assembly method is:

[0015] Prepare 1 mg / mL chitosan solution and κ-carrageenan solution respectively, take a polycarbonate template with a pore size of 600 nm and immerse it in the chitosan solution for 30 minutes, take out the polycarbonate membrane and rinse it three times with deionized water, dry it and soak it in κ-carrageenan solution for 30 minutes, wash it again and dry it; repeat the above steps to assemble 18 layers, finally take the dried polycarbonate membrane with 18 layers assembled and soak it in ethanol, dip a cotton swab in a small amount of aluminum oxide to evenly polish the surface of the polycarbonate membrane; rinse it with deionized water again and dry it, dissolve the template with N, N-dimethylformyl, let it stand for 30 minutes, then wash it with N, N-dimethylformyl 3 times, wash it with ethanol twice, and wash it with deionized water twice to obtain polysaccharide-based microtubules (PMTs).

[0016] In one embodiment of the present invention, in step (1), the method for preparing polysaccharide-based microtubules by pressure assembly method is:

[0017] Take a polycarbonate membrane and lay it flat on the surface of the sand core of the filtration device with the rough surface facing up. Evenly drip 1mL of 1mg / mL chitosan solution on the membrane, open the filtration device to allow the solution to enter the pores of the membrane and attach to the pore wall, then absorb 1mL of 1mg / mL κ-carrageenan solution and drip it on the membrane, and filter through the membrane; between each two filtrations, the template must be rinsed and dried, and the two solutions are alternately passed through the membrane and repeated 18 times, that is, 18 layers are assembled; the polycarbonate membrane is soaked with ethanol, and a cotton swab is dipped in a small amount of aluminum oxide to evenly polish the membrane surface, and then rinsed and dried again with deionized water, and the template is dissolved with N,N-dimethylformyl and allowed to stand for 30 minutes; then washed with N,N-dimethylformyl 3 times, ethanol 2 times, and deionized water 2 times to obtain PMTs.

[0018] In one embodiment of the present invention, in step (2), the preparation method of the enzyme-driven micro-nano motor is:

[0019] Adding glutaraldehyde solution to the polysaccharide microtube, stirring at room temperature, centrifuging, and collecting the precipitated product; wherein the mass concentration of the glutaraldehyde solution is 5%;

[0020] Adding glucose oxidase solution to the precipitated product, stirring at room temperature, standing, centrifuging, and collecting the precipitated product to obtain the enzyme-driven motor; the concentration of the glucose oxidase solution is 1 mg / mL;

[0021] The centrifugal conditions were 10000 r / min, 3 min.

[0022] In one embodiment of the present invention, in step (2), the preparation method of the enzyme-driven micro-nano motor is:

[0023] Add 1 mL of 5% glutaraldehyde solution to 0.2-0.3 mg of PMTs, stir at room temperature for 5 h, stop stirring and let stand overnight, centrifuge at 10,000 r / min for 3 min to remove the supernatant, rinse the precipitate with deionized water to remove residual glutaraldehyde, and collect the precipitate product; then add 1 mL of 2 mg / mL glucose oxidase solution, stir at room temperature for 2 h, stop stirring and let stand overnight in a 4°C refrigerator, centrifuge again to remove the supernatant, and rinse the precipitate twice with deionized water to obtain the enzyme-driven motor, i.e., GOx-PMNMs.

[0024] In one embodiment of the present invention, in step (2), the preparation method of the magnetically driven micro-nano motor is:

[0025] An aqueous solution containing sodium citrate, sodium nitrate and sodium hydroxide is mixed with a ferrous sulfate solution, heated in a water bath, and after the reaction is completed, the ferrosoferric oxide nanoparticles are ultrasonically cleaned with deionized water to prepare ferrosoferric oxide nanoparticles;

[0026] The polysaccharide-based microtubules were immersed in an aqueous solution in which ferroferric oxide was dispersed (the mass ratio of the polysaccharide-based microtubules to ferroferric oxide was 5:1) to obtain a magnetically driven micro-nanomotor.

[0027] In one embodiment of the present invention, in step (2), the preparation method of the magnetically driven micro-nano motor is:

[0028] Use a 50mL three-necked flask as a container, weigh 258mg of sodium citrate, 17g of sodium nitrate, and 160mg of sodium hydroxide and disperse them in 19mL of deionized water, which is called solution A; 556mg of ferrous sulfate heptahydrate is dissolved in 1mL of deionized water, which is called solution B;

[0029] Solution A was mechanically stirred in a 100°C water bath until all the solids were dissolved, and then solution B was added to the flask and the heating reaction was continued for 1 h. After the reaction was completed, the ferrosoferric oxide nanoparticles were ultrasonically cleaned 3 times with deionized water, and the polysaccharide-based microtubes were immersed in 1 mL of an aqueous solution containing ferrosoferric oxide (the mass ratio of polysaccharide-based microtubes to ferrosoferric oxide was 5:1) to obtain Fe-PMNMs.

[0030] In one embodiment of the present invention, in step (2), the preparation method of the platinum-driven micro-nano motor is:

[0031] A NaBH4 aqueous solution is added to a chloroplatinic acid aqueous solution containing polyvinyl pyrrolidone (PVP), stirred at room temperature, to obtain a nano-Pt solution; Pt is precipitated in the form of a precipitate, dispersed in the aqueous solution after centrifugation; polysaccharide-based microtubes are immersed in the aqueous solution in which nano-Pt is dispersed (the mass ratio of polysaccharide-based microtubes to Pt is 5:1) to obtain a platinum-driven micro-nanomotor.

[0032] In one embodiment of the present invention, in step (2), the preparation method of the platinum-driven micro-nano motor is:

[0033] 3.47 mg of polyvinyl pyrrolidone (PVP) was added to 1.03 mL of chloroplatinic acid solution (100 mM), and deionized water was added to make the final volume 3.33 mL. This solution was recorded as solution C. 1.17 mg of NaBH4 was dissolved in 2 mL of water to prepare solution D.

[0034] Under magnetic stirring, solution D was slowly added to solution C, and after sufficient stirring for 12 hours, a nano-Pt solution was obtained. Pt was precipitated in the form of a precipitate and dispersed in the aqueous solution after centrifugation. The polysaccharide-based microtubules were immersed in 1 mL of an aqueous solution in which nano-Pt was dispersed (the mass ratio of the polysaccharide-based microtubules to Pt was 5:1) to obtain Pt-PMNMs.

[0035] The second object of the present invention is to provide a natural polysaccharide-based micro-nanomotor prepared by the above preparation method.

[0036] The second object of the present invention is to provide an application of the above-mentioned natural polysaccharide-based micro-nanomotor as a carrier for delivering curcumin.

[0037] The purpose of the present invention is to prepare a micro-nano motor with self-driving ability by a simple, fast and pollution-free method. A new strategy based on polysaccharide micro-nano motors as carriers for delivering curcumin is proposed. Cationic chitosan and anionic κ-carrageenan are used as raw materials, and polysaccharide-based micro-nano motors are prepared by template method. Then the morphology and structure of the micro-nano motor are characterized, and the motion performance, photothermal conversion performance and safety of the micro-nano motor are evaluated. The electrostatic combination of chitosan and κ-carrageenan forms a tubular structure under the constraint of the template. After modification with magnetic nanoparticles and glucose oxidase, micro-nano motors with uniform size and good dispersibility are prepared. Magnetically driven polysaccharide-based micro-nano motors (Fe-PMNMs), platinum-driven polysaccharide-based micro-nano motors (Pt-PMNMs), and enzyme-driven polysaccharide-based micro-nano motors (GOx-PMNMs) can achieve self-driving by relying on magnetic fields, hydrogen peroxide, and substrate concentration gradients. The prepared micro-nano motors have good biocompatibility. After successfully constructing magnetically driven, platinum-driven, and enzyme-driven micro-nanomotors, we loaded curcumin, a food active ingredient with anti-inflammatory activity, through hydrophobic interactions to simulate in vitro self-driving, and evaluated the stability and bioaccessibility of the micro-nanomotor-curcumin loading system under different conditions. Micro-nanomotors, as carriers of curcumin, have a certain anti-degradation effect on it. Compared with free curcumin, the micro-nanomotor-curcumin loading system has stronger thermal stability and photostability. Curcumin is released slowly in simulated gastrointestinal fluid, which helps the absorption of intestinal epithelial cells and significantly improves bioaccessibility. The micro-nanomotor loaded with curcumin did not show toxicity. An LPS-induced RAW264.7 macrophage in vitro inflammation model was established to evaluate the anti-inflammatory activity of the micro-nanomotor-curcumin loading system. After successful modeling, cellular oxidative stress and inflammatory response were monitored. Treatment with the micro-nanomotor-curcumin loading system can significantly inhibit the expression of ROS in macrophages, effectively reduce oxidative stress damage, and reduce the secretion of inflammatory mediators NO and inflammatory factors such as TNF-α, IL-6, and IL-1β. Compared with curcumin, this loading system can significantly reduce the inflammatory response and show a synergistic protective effect.

[0038] The beneficial technical effects of the present invention are:

[0039] The present invention uses food-grade raw material polysaccharides and a simple, fast and safe template method to prepare natural polysaccharide-based self-driven micro-nanomotors. Then, a polysaccharide-based micro-nanomotor-curcumin loading system is successfully constructed to verify the ability of micro-nanomotors as carriers to protect the encapsulated components and enhance the biological activity. This shows that micro-nanomotors can be used as a new type of food carrier to construct a food delivery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a bright field microscope image of the polysaccharide-based micro-nanomotor.

[0041] Figure 2 This is a scanning electron microscope image of the polysaccharide-based micro-nanomotor.

[0042] Figure 3 This is the energy spectrum of polysaccharide-based micro-nanomotors.

[0043] Figure 4 This is the infrared spectrum of polysaccharide-based micro-nanomotors.

[0044] Figure 5 This is the motion trajectory of the bubble-driven micro-nanomotor.

[0045] Figure 6 This is the motion trajectory of the magnetically driven micro-nanomotor.

[0046] Figure 7 Diffusion coefficients of enzyme-driven micro-nanomotors.

[0047] Figure 8 This is a bar graph showing the changes in RAW264.7 cell viability with the concentration of polysaccharide-based micro-nanomotors.

[0048] Fig. 9 The biochemical analysis was performed after blood samples were taken from mice 14 days after gavage.

[0049] Fig.10 These are the main organ tissue sections of mice in each group.

[0050] Fig.11 Fluorescence image of polysaccharide-based micro-nanomotors loaded with curcumin.

[0051] Fig.12 The loading amount of curcumin on polysaccharide-based micro-nanomotors at different reaction times.

[0052] Fig.13 The curcumin release of polysaccharide-based micro-nanomotors at different pH values.

[0053] Fig.14 Thermal stability of curcumin loaded on micro-nanomotors.

[0054] Fig.15 Photostability of curcumin loaded micro-nanomotors.

[0055] Fig.16 For stability in simulated digestive fluid – and bioaccessibility.

[0056] Fig.17 In vitro antioxidant activity of micro-nanomotors loaded with curcumin.

[0057] Fig.18 In vitro anti-inflammatory activity of micro-nanomotors loaded with curcumin.

[0058] Fig.19Infrared thermal image and photothermal heating curve.

[0059] Fig. 20 for the heating and cooling curves.

[0060] Fig.21 This is a diagram of the effect of extracorporeal photothermal therapy. DETAILED DESCRIPTION

[0061] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0062] Example 1

[0063] The polysaccharide-based microtubules are prepared by a template method, comprising the following steps:

[0064] Take a piece of polycarbonate film and lay it on the surface of the sand core of the suction filtration device. Evenly drip 1mL of 1mg / mL CS solution onto the membrane, open the suction filtration device, allow the solution to enter the membrane pores and adhere to the pore walls; draw another 1mL of 1mg / mL κ-CG solution onto the membrane and continue filtering; rinse the template clean and dry it between each suction, and alternately pass the two solutions through the membrane, repeat 18 times, that is, assemble 18 layers; soak the polycarbonate membrane with ethanol, and immerse a small amount of Al2O3 in the cotton swab to make the membrane surface evenly sanded, wash the template again with deionized water and dry it, dissolve the template with DMF, and let it stand for 30 minutes; then wash it with DMF 3 times, ethanol 2 times, and deionized water 2 times to obtain PMTs.

[0065] Example 2

[0066] A method for preparing a magnetically driven micro-nano motor comprises the following steps:

[0067] Use a 50mL three-necked flask as a container, weigh 258mg of sodium citrate, 17g of sodium nitrate, and 160mg of sodium hydroxide and disperse them in 19mL of deionized water, which is called solution A; 556mg of ferrous sulfate heptahydrate is dissolved in 1mL of deionized water, which is called solution B;

[0068] Solution A was mechanically stirred in a 100°C water bath until all the solids were dissolved, and then solution B was added to the flask and the heating reaction was continued for 1 hour. After the reaction was completed, the ferrosoferric oxide nanoparticles were ultrasonically cleaned 3 times with deionized water; the polysaccharide-based microtubes were immersed in 1 mL of an aqueous solution containing ferrosoferric oxide (the mass ratio of polysaccharide-based microtubes to ferrosoferric oxide was 5:1) to obtain Fe-PMNMs.

[0069] Example 3

[0070] A method for preparing a platinum-driven micro-nano motor comprises the following steps:

[0071] 3.47 mg of polyvinyl pyrrolidone (PVP) was added to 1.03 mL of chloroplatinic acid solution (100 mM), and deionized water was added to make the final volume 3.33 mL. This solution was recorded as solution C. 1.17 mg of NaBH4 was dissolved in 2 mL of water to prepare solution D. Under magnetic stirring, solution D was slowly added to solution C, and the nano-Pt solution was obtained after sufficient stirring for 12 hours. Pt was precipitated and dispersed in the aqueous solution after centrifugation. The polysaccharide-based microtubules were immersed in 1 mL of aqueous solution dispersed with nano-Pt (the mass ratio of polysaccharide-based microtubules to Pt was 5:1) to obtain Pt-PMNMs.

[0072] Example 4

[0073] A method for preparing an enzyme-driven micro-nano motor comprises the following steps:

[0074] 1 mL of 5% glutaraldehyde solution was added to Example 1, and the mixture was stirred at room temperature for 5 h, then stopped stirring and allowed to stand overnight. The supernatant was removed by centrifugation at 10,000 r / min for 3 min, and the precipitate was rinsed with deionized water to remove residual glutaraldehyde. Then 1 mL of 2 mg / mL glucose oxidase solution was added, and the mixture was stirred at room temperature for 2 h. After stopping stirring, the mixture was placed in a 4°C refrigerator and allowed to stand overnight. The supernatant was removed by centrifugation again, and the precipitate was rinsed twice with deionized water to obtain GOx-PMNMs.

[0075] Test example:

[0076] (1) Microscope bright field image, scanning electron microscope image and energy spectrum image

[0077] The samples prepared in Examples 1, 2, 3, and 4 were first dispersed by low-frequency ultrasound, and then immersed in 2.5% glutaraldehyde phosphate buffer for fixation. After the samples were dehydrated with gradient ethanol for 15 minutes, 10 μL was dripped onto a 3 mm × 3 mm silicon wafer and dried at room temperature. Subsequently, gold was plated using an ion sputtering instrument, and electron microscopy and energy spectrum scanning were performed under an accelerating voltage. The results are shown in FIG. Figure 1-3 As shown, the basic morphology of PMTs and PMNMs prepared by Examples 1, 2, 3, and 4 can be seen through the light field map of the optical microscope. The length of the nanotubes is about 9 μm. Since both matrix materials are polysaccharides with a certain viscosity, the microtube pores are prone to crosslinking and agglomeration after polishing, so there is a partial adhesion phenomenon. After modification with Fe3O4 and Pt nanoparticles, the dispersion effect is better. The scanning electron microscopy results can more clearly observe the hollow tubular structure of PMNMs. It can be determined that its length is 9 μm and its diameter is about 600 nm. The length of the microtubes is relatively uniform, consistent with the template size. The energy spectrum shows that Fe3O4 and Pt nanoparticles successfully modified PMT. Metal nanoparticles are attached to one end of Fe-PMNMs and Pt-PMNMs to form an asymmetric structure, which provides power for their movement.

[0078] (2) Infrared spectrum

[0079] The molecular structures of PMTs and PMNMs were characterized by infrared spectroscopy. The samples prepared in Examples 1, 2, 3, and 4 were dispersed in ethanol, and a few drops were dripped into the sample plate using a glass rod. After air drying, the samples were scanned with an infrared spectrometer to analyze the changes in their functional groups and determine the interaction between the components. The results are shown in Figure 2. Figure 4 As shown in the figure, it can be seen that κ-CG, CS and pmt are in the range of 3600-3300 cm -1 The absorption peaks in the range are caused by the stretching vibrations of -OH and -NH2. -1 The absorption peaks near 1663 cm are caused by CH in the complex (derived from -CH and -CH2). The absorption peaks of CS and κ-CG are weak, while the absorption peaks of binary and ternary complexes are more obvious. -1 and 1594cm -1 The characteristic absorption peaks at 1648 cm-1 belong to the stretching vibration of amide I band (CO) and amide II band (-NH) of CS. -1 The absorption peak of κ-CG at 1659 cm-1 is derived from polymer-bound water, which is superimposed on the amide bond of chitosan in the mixture sample. -1 , and exists in other ternary complexes. PMT at 1049cm -1 The absorption peak at 893 cm-1 is derived from the vibration of the glycosidic bond (COC) or the bending vibration of -OH. -1 The absorption peak at 845 cm-1 is derived from the NH bending vibration, and the absorption peak of κ-CG at 845 cm-1 is derived from the NH bending vibration. -1 The absorption peak at 881 cm-1 is derived from the position of the secondary sulfate (COS) on the C-4 axis of galactose, and the absorption peak of PMTs shifts to 881 cm-1. -1 , indicating that CS and κ-CG are successfully cross-linked. The infrared spectra of Pt-PMNMs, GOX-PMNMs and Fe-PMNMs are close to those of PMTs, indicating that the incorporation of Pt, GOX and Fe3O4 does not produce new chemical bonds or functional groups and will not have a significant impact on the main structure of PMTs.

[0080] (3) Driving motion trajectory and diffusion coefficient

[0081] An external magnet was used to manipulate the movement of the sample prepared in Example 2. Hydrogen peroxide solution was used as a catalyst on the sample prepared in Example 3 to induce bubble formation to drive its own movement. The movement speed of the sample prepared in Example 4 was regulated by the concentration of the glucose solution. DLS was used to measure the diffusion coefficient of the enzyme-driven motor in the substrate solution to characterize the changes in the movement state of GOx PMNMs (N=3). An inverted fluorescence microscope was used to capture the movement video and image of a single PMNM, which was then analyzed using VideoSpot Tracker software to track its movement trajectory. The results are shown in Figure 2. Figure 5-7 As shown in Figure 2, the motion trajectory of Pt-PMNMs within 0.35 s (0.07 s / fps) is as follows: Figure 5 As shown. The Pt nanoparticles on the microtubule motor catalyze the decomposition of hydrogen peroxide to produce oxygen bubbles, which are released from one end of the tube, causing the microtubule motor to move rapidly. The bubble trajectory shows that the microtubule motor performs irregular bending movements in the solution. The concentration of hydrogen peroxide fuel has a certain effect on the speed of the motor. The controllable movement of Fe-PMNMs promotes the targeted transport of bioactive substances such as Figure 6 As shown in the figure, magnetic nanoparticles are assembled at one end of the tube, and under the guidance of the magnet, the Fe-PMNMs exhibit 360° clockwise rotation. Applying different types of magnetic fields around PMNMs can control their motion state. Figure 7 As shown, the trajectory of GOx-PMNMs in 0 and 80mmol / L glucose solutions lasting 10s. At a substrate concentration of 0mmol / L, it can be observed that the motor only exhibits short-range forward and backward random motion, called Brownian motion. After the addition of the micro-nanomotor to the glucose solution, a significantly elongated motion path can be observed, indicating a clear directionality in the motion. The diffusion coefficient of GOx-PMNMs measured by DLS in the two solutions increased significantly from 0.43±0.01 to 0.65±0.01. The enhancement of the motility and diffusion capacity of GOx-PMNMs indicates that the catalytic reaction between the micro-nanomotor and the glucose substrate can improve the motility of the micro-nanomotor.

[0082] (4) Safety evaluation

[0083] The Shimi Li method was used to determine cell viability, and RAW264.7 cells in the logarithmic growth phase were selected for in vitro toxicity tests. The cells were placed in DMEM high-glucose medium containing 10% serum and 1% penicillin-streptomycin solution. When the cell growth density reached 80%, 1×10 4The cells were seeded in a 96-well cell culture plate at a density of 100 cells / well and cultured for 24 h. Then, gradient concentrations of PMTs, Fe-PMNMs, Pt-PMNMs and GOx-PMNMs were added and cultured for another 24 h. The plate was washed with PBS and incubated with CCK-8 reagent for 4 h. The absorbance was measured at 450 nm. The cell viability was calculated according to the formula. The results are shown in Figure 8 shown.

[0084] In order to detect the in vivo toxicity of PMNMs, 50 4-week-old BALB / c mice were divided into 5 groups. The control group was gavaged with 0.3 mL of water, and the experimental groups were gavaged with 0.3 mL of PMTs, Fe-PMNMs, Pt-PMNMs, and GOx-PMNMs. The feeding cycle of mice was 14 days. In the experiment, mice were housed individually in cages with free access to food and water. The mental state and diet of mice were observed on days 0, 7, and 14. Blood samples were taken from the mouse eyeballs and centrifuged at 4000 r / min for 15 min to obtain serum. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid (UA), high-density lipoprotein cholesterol (HDL-C), and total cholesterol (T-CHO) were detected using a kit. The results are shown in Fig. 9 The heart, liver, spleen, lung, kidney, and stomach tissues of the mice were taken after they were killed, fixed in formaldehyde solution, processed into slices, and stained with hematoxylin and eosin (HE) to observe whether there were any lesions or abnormalities, such as Fig.10 shown.

[0085] The safety evaluation diagram of the polysaccharide-based micro-nanomotors prepared in Examples 1, 2, 3, and 4 is shown in FIG. Figure 8-10 As shown, Figure 8 As shown in the figure, when the concentration of PMT, Fe-PMNM, Pt-PMNM and GOx-PMNM was 10μg / mL, the cell viability was about 99%, and there was no significant difference among the groups, indicating that at a concentration of 10μg / mL, PMTs and PMNMs were non-toxic to cells; when the concentration of PMTs, Fe-PMNMs and GOx-PMNMs increased to 400μg / mL, the cell viability of PMTs, Fe-PMNMs, Pt-PMNMs and GOx-PMNMs decreased to 96.63%, 94.61% and 95.30%, respectively. In general, the cell viability of the PMNM-treated group gradually decreased as the sample concentration increased from 10μg / mL to 400μg / mL, but even after co-incubation at 400μg / mL for 24h, the cell survival rate was still above 90%, indicating that PMNMS has low cytotoxicity.

[0086] After 14 days of gavage, blood samples were taken from mice for biochemical analysis. Fig. 9As shown, (a) serum alanine aminotransferase / glutamate acetone aminotransferase (ALT / GPT), (b) aspartate aminotransferase (AST / GOT), (c) uric acid, (d) high-density lipoprotein cholesterol (HDL-C), (e) total cholesterol (T-CHO); it can be seen from the figure that there was no statistically significant difference in the levels of ALT, AST, UA, HDL-C, and T-CHO in the serum of mice in each sample group and the blank control group (p>0.05), indicating that PMNMs had no damage to liver and kidney function. HE staining showed that the gastric tissue structure of mice in each group was clear, the gastric mucosa and fundic glands were closely arranged, and no bleeding, shedding or inflammatory cell infiltration was observed. Liver and kidney microscopy showed that there were no abnormalities in the kidneys of the normal control group and the specimen group, no abnormal changes were found in the renal cortical glomerular capillaries, the tubular epithelial cells and tubular wall cells were normal in morphology, and the boundaries of the renal bodies were clear. Under the microscope, the liver lobule structure of the normal control group and the sample group was intact and normal, the outline of the liver parenchymal cells was clear and normal, the nuclei and cytoplasm cells were evenly distributed, and the liver cells were arranged in an orderly manner; the spleen tissue sections showed clear spleen follicle structure, the spleen tissue was normal, and there was no obvious damage to the heart tissue ( Fig.10 ). The results of cytotoxicity test and serum biochemical index determination showed that PMNMs had good biocompatibility and low toxicity, suggesting that PMNMs can be used as a non-toxic carrier of bioactive substances.

[0087] (5) Load capacity

[0088] ① Prepare Cur solutions with different dilution ratios and draw a standard curve. Take 0.4 mg PMTs, Fe-PMNMs, Pt-PMNMs, GOx-PMNMs and mix with 1 mL 0.1 mg / mL curcumin standard solution, stir for 1, 2, 4, 6, and 12 hours in the dark. Centrifuge at 8000 rpm for 3 minutes, separate PMTs and PMNMs-Cur from the supernatant, wash twice with deionized water, and combine with the supernatant, and measure the absorbance at 429 nm. Calculate the loading rate of Cur according to the standard curve.

[0089] Figure 11-12 The following are the fluorescence images of polysaccharide-based micro-nanomotors loaded with curcumin and the loading amount of curcumin at different reaction times. Fig.12 It can be seen that after GOx, Fe3O4 and Pt loading, the loading amount reaches 44.52μg / mg, which is relatively low. This may be due to the fact that the particles on the PMT surface occupy the sites where Cur binds to PMT, that is, the number of active sites decreases. As the reaction time increases, depolymerization occurs and the loading decreases.

[0090] ② In order to study the release ability of PMNMs-Cur, it was dispersed in buffer solutions of different pH values ​​to simulate the gastrointestinal environment. About 0.4 mg of PMNMs-Cur was placed in buffer solutions of pH 1.2 and pH 6.8 respectively. After incubation at 37°C for 2 hours, the supernatant was taken and the release rate of Cur was determined by UV spectrophotometry.

[0091] Fig.13 The curcumin release of polysaccharide-based micro-nanomotors at different pH values, where the red line: initial curcumin concentration; the blue line: release curve at pH = 6.8; the purple line: release curve at pH = 1.2.

[0092] After successfully loading Cur, the release characteristics of the PMNM–Cur loading system were measured. As can be seen from the curve, Cur has an obvious absorption peak at 429nm, which is its characteristic peak. In an acidic buffer solution with a pH of 1.2, the release rate is lower than that in a neutral buffer solution. In a buffer solution with a pH of 6.8, Cur will be degraded, which will lead to the desorption of Cur on PMNMs. Its release rate is about 30% (32.97% for PMTs, 33.11% for Fe-PMNMs, and 32.52% for Pt-PMNMs). GOx-PMNMs has the lowest release rate of 17.68%, which may be due to the network structure formed by CS and GOx cross-linked by glutaraldehyde, which hinders the diffusion of Cur molecules into the release medium and slows down the diffusion rate of Cur.

[0093] (6) Thermal stability and light stability

[0094] Free curcumin was used as the control group and PMNMs-Cur was used as the sample group. They were placed in a transparent glass vial, heated at 85°C, and samples were taken at 30, 60, 90, 120, 150, and 180 min, and immediately cooled to room temperature, and then the absorbance was measured at 429 nm. Its retention rate was calculated based on the standard curve.

[0095] 1 mL of curcumin solution (0.1 mg / mL dissolved in anhydrous ethanol) and an equal volume of PMNMs-Cur solution were added to a transparent glass bottle and irradiated with UV light for 120 min. Samples were taken and recorded in turn at Cur concentrations of 20, 40, 60, 80, 100 and 120 min away from light. The retention rate was calculated based on the standard curve.

[0096] Figure 14-15 Thermal and photostability experiments of curcumin loaded on micro-nanomotors, such as Fig.14As shown in (a) the retention rate (%) of curcumin in the sample after heat treatment at 85°C and (b) the degradation curve, it can be seen that the retention rate of curcumin in the sample after heat treatment at 85°C, after heating at 85°C for 30, 60, 90, 120, 150, and 180 min, the retention rate of free Cur decreased rapidly, and the retention rate at 3h was 54.9%. After heating, the retention rate of Cur increased after loading Cur on PMT and PMNMs, indicating that the protective effect of PMT is beneficial to Cur. Fig.15 Shown are the retention rate of curcumin in the sample after illumination, (a) the retention rate of curcumin in the sample after illumination (%) and (b) the degradation curve; after loading Cur on PMTs and PMNMs, the retention rate of Cur was slightly improved, and the retention rate of Cur by PMTs and GOx-PMNMs was higher than that of Fe-PMNMs and PtPMNMs.

[0097] (7) Simulated digestion stability

[0098] 5mL sample solution prepared by embodiment 1,2,3,4 and an equal amount of curcumin aqueous solution were placed in a conical flask, 20mL of 0.1mol / L hydrochloric acid solution (pH 1.2) was added, then the reaction mixture was incubated in a shaking table at 37°C and 90rpm for 10min, 5mg of pepsin was subsequently added to simulate gastric digestion, and after incubation for 60min, the gastric digestive fluid pH was adjusted to 7.0 with 4mol / L sodium hydroxide solution, and 125mg of bile salt extract was added to incubate for 10min. Finally, 10mg of pancreatic enzyme was added to simulate small intestinal digestion for 120min. After digestion was completed, 1mL of digestive fluid was taken and centrifuged at 10000rpm for 30min at 4°C, and the absorbance of the supernatant was measured at a wavelength of 429nm, and the curcumin content was measured with reference to the standard curve to calculate the bioavailability of curcumin.

[0099] Fig.16 (a) Stability of free Cur and PMNMs-Cur in simulated digestive fluid; (b) Bioaccessibility of free curcumin and PMNMs-Cur. Fig.16(a) shows the degradation of free curcumin, PMT-Cur, Fe-PMNMs-Cur, Pt-PMNMs-Cur and GOx-PMNMs-Cur by curcumin in the digestive system. In the simulated gastric digestion stage, free curcumin was released rapidly, while curcumin in PMNMs was released slowly, indicating that PMNMs had a significant protective effect on curcumin. The cumulative release rates of PMTs-Cur, Fe-PMNMs-Cur, Pt-PMNMs-Cur and Gox-PMNMs-Cur in gastric juice for 60 min were 21.07%, 22.17%, 19.40% and 9.75%, respectively. In the simulated intestinal digestion stage, the release of curcumin gradually increased with the extension of digestion time. At this time, under the action of pancreatic enzymes and bile extracts, free curcumin was dispersed in the digestive juice in the form of mixed micelles, and its release rate was about 57.49%, while the release rate of curcumin in nano-sport carriers was 19.98-34.47%. Under the protection of nano-sport molecules, curcumin can stay in the small intestine for a longer time, promote the absorption of intestinal epithelial cells, and thus improve the bioavailability of polyphenolic compounds. The bioaccessibility of free curcumin is 44.64%. The bioaccessibility of curcumin in PMTs-Cur, Fe-PMNMs-Cur, Pt-PMNMs-Cur and GOx-PMNMs-Cur was increased to 70.36%, 68.82%, 70.94% and 84.04%, respectively. Compared with free curcumin, the bioaccessibility of PMNMs to curcumin was increased by 1.8 times.

[0100] (8) Anti-inflammatory activity

[0101] RAW264.7 cells were cultured at 2 × 10 5 mL -1 The cells were inoculated at a density of 1 μg / mL in a 12-well plate and cultured until adherent. A blank control group, LPS model group (1 μg / mL), pure curcumin control group (20, 40, 80 μg / mL), PMTs control group (150, 300, 600 μg / mL), and PMNMs-Cur administration group (20, 40, 80 μg / mL. The concentrations were uniformly quantified according to the curcumin concentration) were set up. The three concentrations in each group were used as low, medium, and high dose groups, respectively. Pure curcumin, PMNMs, and PMNMs–Cur were added in advance at the above dose concentrations to incubate RAW264.7 cells for 2 h. Subsequently, except for the blank group, the cells were stimulated with LPS (1 μg / mL) for 24 h in all other groups. Diluted DCFH-DA probe was added and incubated at 37°C for 20 min. The cells were washed twice with PBS to fully remove the DCFH-DA that did not enter the cells. Imaging was performed using an upright and inverted fluorescence microscope, and the average fluorescence intensity of the obtained atlas was analyzed using Image J.

[0102] RAW264.7 cells were collected at 2×10 5 Cell mL -1 The cells were inoculated in a 12-well plate at a density of 100 μg / mL and cultured until adhered. According to the experimental steps of Example 15, pure curcumin, PMTs, PMTs-Cur, Fe-PMNMs-Cur, Pt-PMNMs-Cur and GOx-PMNMs-Cur were added to pre-incubate RAW264.7 cells for 2 h, and then, except for the blank group, the remaining groups were stimulated with LPS (1 μg / mL) for 24 h, and the cell supernatant was removed. Different ELISA kits were used to detect the levels of TNF-α, IL-6, IL-1β and NO in the supernatant of macrophage RAW264.7 in each group. The operation method should be strictly in accordance with the instructions of the corresponding kit.

[0103] Figure 17-18 Evaluation of the antioxidant and anti-inflammatory properties of PMNMs-Cur in vitro. Fig.17 (a) ROS imaging in RAW264.7 cells after different treatments, (b) mean fluorescence intensity results after software analysis; Fig.18 (a) Effect of PMNMs-Cur on cellular NO content, (bd) Effect of PMNMs-Cur on cellular pro-inflammatory factor levels.

[0104] As can be seen from the figure, after LPS treatment, the morphology of RAW264.7 cells changed significantly from round to conical, and the cells were damaged by oxidative stress. Fluorescence microscopy showed that the LPS-stimulated cells showed bright green fluorescence, indicating the generation of ROS ( Fig.17 a). In contrast, Cur, PMTs, and PMNMs-Cur resulted in a significant decrease in intracellular fluorescence intensity (p<0.05). PMNMs-Cur showed a synergistic effect of Cur and PMNMs ( Fig.17 b). The levels of NO, TNF-α, IL-6 and IL-1β in the supernatant of RAW264.7 macrophages in the LPS model group were significantly increased (p<0.01), indicating that LPS stimulation successfully induced cellular inflammatory response ( Fig.18 ad). Fe-PMNMs-Cur, Pt-PMNMs-Cur and GOx-PMNMs-Cur at low, medium and high dose concentrations significantly inhibited the production of three pro-inflammatory factors (p<0.01). Compared with the pure curcumin group, all doses of PMNMs-Cur increased the inhibitory effect on cellular inflammation. The anti-inflammatory effect of PMTs was significantly lower than that of PMNMs-Cur group, indicating that PMNMs-Cur can improve the inflammatory response of LPS-induced RAW264.7 macrophages and play an anti-inflammatory role.

[0105] (9) Photothermal performance

[0106] 1 ml of sample solution was added to a transparent glass bottle, and an 808 nm near-infrared laser was installed 5 cm above the bottle. The PMNMs suspension was irradiated with near-infrared laser for 10 min, and the temperature change of the sample was detected with an infrared temperature gun. The temperature changes of Fe-PMNMs and Pt-PMNMs were monitored under near-infrared irradiation for 10 min and natural cooling for 10 min after the laser was turned off, and the photothermal conversion efficiency of the two PMNMs was calculated.

[0107] The cells were cultured in DMEM high-glucose medium containing 10% serum and 1% penicillin-streptomycin solution. When the growth density reached 80%, 1×10 4 The cells were inoculated at a density of 100 μg / mL in a 96-well cell culture plate. After culturing for 24 h, gradient concentrations of PMTs, Fe-PMNMs, and Pt-PMNMs were added and cultured for another 24 h. Hep G-2 cells were irradiated with 808 nm near-infrared laser for 10 min and the cell viability was determined by CCK-8 method after culturing for 4 h.

[0108] Figure 19-21 For in vitro photothermal performance evaluation; Fig.19 (a) At 808 nm, 2 W / cm 2 Infrared thermal images of water, PMTs, Fe-PMNMs, and Pt-PMNMs when the laser irradiation lasts for 10 min and the sample concentration is 400 μg / mL. (b) Infrared thermal images of water, PMTs, Fe-PMNMs, and Pt-PMNMs when the laser irradiation power density is 2 W / cm 2 Photothermal heating curves of water, PMTs, Fe-PMNMs and Pt-PMNMs under 808nm laser irradiation. Fig. 20 (a) Heating and cooling curves of Fe-PMNMs under three NIR switching cycles, (b) heating and cooling curves of Pt-PMNMs under three NIR switching cycles. Fig.21 (a) Bar graph showing the changes in the viability of liver cancer cells (HepG-2) with the concentrations of PMTs and PMNMs under near-infrared laser irradiation; (b) liver cancer cells (HepG-2) were treated with different concentrations of PMTs, Fe-PMNMs and Pt-PMNMs.

[0109] Starting from room temperature, the near-infrared laser (2.0 W / cm 2 , 808nm) irradiation for 10 minutes ( Fig.19 a). Comparison of the photothermal performance of Fe-PMNMs and Pt-PMNMs, such as Fig.19As shown in b. When the concentration was 400 μg / mL, Fe-PMNMs heated up to 58.7°C after 10 minutes of illumination, while Pt-PMNMs heated up to 55.3°C. Fe-PMNMs heated up only slightly more than Pt-PMNMs. This shows that after Fe3O4 nanoparticles and Pt nanoparticles were loaded on the PMT surface, the photothermal conversion performance of the microtubes was significantly improved. Under the same conditions, the temperature change of the blank group aqueous solution was less than 4.2°C. Finally, the heating-cooling cycle mode of the two PMNMs was tested ( Fig. 20 ), and still had good photothermal performance after three heating-cooling cycles. The calculated photothermal conversion efficiencies of Fe-PMNMs and Pt-PMNMs were 34.12% and 32.05%, respectively. This result shows the applicability of Fe-PMNMs and Pt-PMNMs in photothermal therapy. In contrast, Fe3O4 nanoparticles have better photothermal performance and lower cost than Pt nanoparticles. Based on the study of photothermal properties, we also studied the in vitro photothermal therapeutic effects of Fe-PMNMs and Pt-PMNMs. First, the toxicity of the motor itself to HepG-2 cells was determined ( Fig.21 a). With the increase of PMT and PMNM concentrations, the survival rate of HepG-2 cells decreased slightly, but even at a concentration of 400 μg / mL, the cell survival rate was still above 89% after 24 h of co-incubation. After HepG-2 cells were co-incubated with materials of different concentrations, laser (808 nm, 2 W / cm 2 ) irradiation. Fig.21 As shown in (b), the cell survival rate decreased significantly with the increase of material concentration. When the concentration of Fe-PMNM and Pt-PMNM was 400μg / mL, the cell survival rate was as low as 19.08% and 23.31%, respectively. This suggests that PMNMs may enter the interior of the cell through internalization and endocytosis. The heat generated in the presence of near-infrared laser promotes the increase in temperature in the irradiated area. At lower concentrations, when the substance can only affect a small amount of protein, the temperature inside the cell is low. When the concentration of PMNMs in the cell is high, the heat will accumulate to a certain extent, causing the cell membrane of cancer cells to disintegrate and the protein to denature. This will induce processes such as cell apoptosis and necrosis, resulting in a decrease in cell survival rate. The photothermal conversion efficiency of Fe-PMNMs is slightly higher than that of Pt-PMNMs, and its cell killing effect is also stronger, which is consistent with the results of photothermal conversion efficiency.

[0110] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a natural polysaccharide-based micro-nanomotor, characterized in that: The steps include: (1) Preparation of polysaccharide-based microtubules: Using a polycarbonate membrane as a template, an alternating assembly layer of chitosan and κ-carrageenan is formed on the template by an immersion assembly method or a pressure assembly method, and then the template is washed away to obtain polysaccharide-based microtubules; (2) Preparation of micro-nanomotors: Glucose oxidase is cross-linked to polysaccharide microtubules by glutaraldehyde cross-linking method to form enzyme-driven micro-nanomotors; alternatively, ferroferric oxide is cross-linked to polysaccharide microtubules to form magnetically driven micro-nanomotors; alternatively, nanoplatinum is cross-linked to polysaccharide microtubules to form platinum-driven micro-nanomotors.

2. The preparation method according to claim 1, characterized in that: In step (1), the pore size of the polycarbonate membrane is 600 nm and the thickness is 9 μm.

3. The preparation method according to claim 1, characterized in that: In step (1), the immersion assembly method is as follows: the template is repeatedly and alternately immersed in a chitosan solution and a κ-carrageenan solution to perform self-assembly; then the template is washed away to obtain polysaccharide-based microtubules.

4. The preparation method according to claim 1, characterized in that: In step (1), the pressure assembly method is: chitosan solution and κ-carrageenan solution are repeatedly and alternately added to the template, and then filtered and assembled; then the template is washed away to obtain polysaccharide-based microtubules.

5. The preparation method according to claim 3 or 4, characterized in that: The concentration of the chitosan solution was 1 mg / mL; the concentration of the κ-carrageenan solution was 1 mg / mL; and the template was dissolved using N,N-dimethylformyl.

6. The preparation method according to claim 1, characterized in that: In step (2), the preparation method of the enzyme-driven micro-nano motor is: Adding glutaraldehyde solution to the polysaccharide microtube, stirring at room temperature, centrifuging, and collecting the precipitated product; wherein the mass concentration of the glutaraldehyde solution is 5%; Add glucose oxidase solution to the precipitated product, stir at room temperature, let stand, centrifuge, collect the precipitated product, and obtain the enzyme-driven motor; the concentration of the glucose oxidase solution is 1 mg / mL.

7. The preparation method according to claim 1, characterized in that: In step (2), the preparation method of the magnetically driven micro-nano motor is: An aqueous solution containing sodium citrate, sodium nitrate and sodium hydroxide is mixed with a ferrous sulfate solution and heated in a water bath. After the reaction is completed, the ferroferric oxide nanoparticles are ultrasonically cleaned with deionized water to obtain ferroferric oxide nanoparticles; polysaccharide-based microtubes are immersed in the aqueous solution dispersed with ferroferric oxide to obtain magnetically driven micro-nanomotors.

8. The preparation method according to claim 1, characterized in that: In step (2), the preparation method of the platinum-driven micro-nano motor is: The NaBH4 aqueous solution is added to the chloroplatinic acid aqueous solution containing polyvinyl pyrrolidone and stirred at room temperature to obtain a nano-Pt solution; Pt is precipitated in the form of a precipitate and dispersed in the aqueous solution after centrifugation; the polysaccharide-based microtube is immersed in the aqueous solution dispersed with nano-Pt to obtain a platinum-driven micro-nano motor.

9. A natural polysaccharide-based micro-nano motor prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the natural polysaccharide-based micro-nanomotor according to claim 9, characterized in that: As a carrier for delivering curcumin.

Citation Information

Patent Citations

  • Method for producing natural polysaccharide-base nanocapsules

    CN102580641A

  • Micro-nanotube and preparation method and application thereof

    CN104016299A

  • Preparation method of corrole modified ferriferrous oxide composite nanomaterial

    CN106000473A

  • Preparation method of nano motor-hydrogel system for gene targeting therapy

    CN112472664A

  • Preparation method and application of glucose oxidase modified iron-based metal organic framework nano drug delivery system

    CN114177311A